Integrasi Pendidikan Akhlak dalam Pelajaran Sejarah Kebudayaan Islam di Kelas IV Madrasah Ibtidaiyah Negeri 3 Kota Metro Lampung: Integration of Moral Education in Islamic Cultural History Lessons in Class IV of Madrasah Ibtidaiyah Negeri 3 Kota Metro Lampung - Muhammad Munir; Muhammad Najib; Amalia Islamiati Putri; Effiana Cahya Ningrum; Fatonah Salfadilah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to explore the integration of moral education in the teaching of Islamic Cultural History at Madrasah Ibtidaiyah Negeri 3 Kota Metro Lampung. The method employed is a field study with a descriptive qualitative approach. Data was gathered through interviews, observations, and documentation. Data analysis was conducted using Miles and Huberman's technique. The findings indicate that the teaching of Islamic Cultural History at the madrasah has successfully integrated both knowledge and moral education. The teachers involved in this study have also provided adequate information and demonstrated effective integration. The academic content, especially regarding historical events and the exemplary behavior of Prophet Muhammad, is well-linked with moral education. The implementation of moral values encompasses courtesy, responsibility, and honesty. These results affirm that integration in teaching relies not only on written materials but also on the active role and exemplary conduct of teachers. Therefore, it is crucial to integrate the concepts of Islamic Cultural History and Moral Education as a means of cultivating noble character in the nation's younger generation.